Uji Coba Konsep Pipa Organa pada Alat Peraga Menggunakan Botol Bekas: Bantuan Aplikasi Phypox - Windi Anggraini; Halimatul Zahra Kurtubi; Nabila Aprilia; Amelia Putri Wardhani; Ahmad Suryadi (UNIVERSITAS SERAMBI MEKKAH, 2024)
Some physics material may be difficult to understand, especially the organ pipe material in the vibration and sound chapter. To help students understand organ pipe material, experiments are very important in its delivery. However, teaching aids and accurate data collection are often a challenge for teachers and students. Testing organ pipes on teaching aids with the help of the Phyphox application can be a method for teaching the physics of sound and vibration practically and interactively. This research was conducted to compare the speed of sound propagation in air and water as well as measure the frequency of tones in air columns with different water heights in bottles using the Phypox application. The frequency data obtained shows that the longer the air column, the higher the frequency produced, conversely the shorter the air column, the lower the frequency produced. The calculation results for the speed of air propagation vary between 234 m/s to 622 m/s, with the closest value to a constant air speed of 340 m/s found in the basic notes Do and Re. Therefore, it is concluded that the teaching aids created can be used to increase students' understanding of the concept of organ pipes and the role of the Phyphox application in increasing the accuracy of data collection.